Mrs Pepperpot Stories - Alf Prøysen; Hilda Offen (Red Fox, 2000)
A fantastic collection of much-loved, classic stories for all the family!Mrs Pepperpot can't choose when she will shrink to the size of a pepperpot - it just happens!